EFFECT OF BRAND DIFFERENTIATION ON COMPETITIVE ADVANTAGE IN NIGERIAN BREWERIES PLC, OGUN STATE - Olufemi A, Ogunkokoya; Banjo A, Hassan; Temitope Ebunola, Sokehinsi (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2020)
The paper investigates the effect of brand differentiation on competitive advantage in Nigerian Breweries Plc, Ogun State. The broad objective of the research is to evaluate the effect of brand differentiation on competitive advantage. Primary source of data was used in carrying out this study. One hundred and sixty-six (166) completely filled and returned copies of questionnaire used as the sample size usable for the study. The data used in this study were generated using a 5-point Likert scale questionnaire. The data generated were analyzed using descriptive statistics, regression analysis with the aid of Statistical Package for the Social Sciences (SPSS) version 17 and conducted at 5% significance level. The finding indicates that brand logo has no significant effect on competitive advantage as reported by hypothesis one; was also revealed that brand name has no significant effect on competitive advantage as suggested by hypothesis two and lastly, it was also observed that brand symbol has no significant effect on competitive advantage. The study concluded that the brand differentiation has a significant effect on competitive advantage in Nigeria Breweries Plc. The study therefore recommends among other that firms must ensure that they improve upon their branding experience for customers, as this goes a long way to improve upon their competitive advantage.